A Reliable Protocol for Wireless Sensor Networks to Support Large-Scale Smart Farm Systems - Pakorn Juleang; S. Mitatha; Sawatsakorn Chaiyasoonthorn (My University, 2024)
This research presents a newly proposed design for a reliable protocol for wireless sensor networks, supporting large-scale smart farms. The protocol was tested and compared with previous methods. The results demonstrated a significantly higher data transmission success rate and a transmission speed approximately three times faster. Additionally, when the proposed reliable protocol was implemented in ten smart farms in Sukhothai province, it achieved a data transmission success rate of 99.07% and an average transmission time of 16.64 seconds, approximately three times faster than the previous method. These experimental outcomes confirm that the proposed reliable protocol meets the communication objectives outlined in its design, ensuring reliable, consistent, and timely data transmission.
Keywords: Food Supply Chain Traceability; Smart Agriculture and AI